2022
DOI: 10.4251/wjgo.v14.i8.1456
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between gut microbiota and COVID-19 impacts pancreatic cancer progression

Abstract: Pancreatic cancer (PC) is one of the most common causes of cancer-associated death worldwide, with a low rate of 5-year survival. Currently, the pathogenesis of PC is complicated, with no efficient therapy. Coronavirus disease 2019 (COVID-19) disease caused by severe acute respiratory syndrome coronavirus 2 further exacerbates the challenge of patients with PC. The alteration of gut microbiota caused by COVID-19 infection may impact PC progression in patients via immune regulation. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Additionally, it has been demonstrated that patients with COVID-19 develop dysbiotic microbiota, potentially heightening the risk for severe COVID-19 and colorectal cancer [117]. In pancreatic cancer (PC), the alteration of gut microbiota caused by COVID-19 infection showed an impact on PC progression via immune regulation [118]. Recently, it was demonstrated that patients with cancer and COVID-19 have a higher chance of severe symptoms, suggesting an association between the naso-oropharyngeal microbiome, breast cancer, and COVID-19 severity [119].…”
Section: Covid-19 and Lung Cancermentioning
confidence: 99%
“…Additionally, it has been demonstrated that patients with COVID-19 develop dysbiotic microbiota, potentially heightening the risk for severe COVID-19 and colorectal cancer [117]. In pancreatic cancer (PC), the alteration of gut microbiota caused by COVID-19 infection showed an impact on PC progression via immune regulation [118]. Recently, it was demonstrated that patients with cancer and COVID-19 have a higher chance of severe symptoms, suggesting an association between the naso-oropharyngeal microbiome, breast cancer, and COVID-19 severity [119].…”
Section: Covid-19 and Lung Cancermentioning
confidence: 99%
“…Gut microbiota plays an important role in many metabolic disorders [ 15 , 124 , 125 ], including obesity. Mechanistic studies show that gut microbiota can impact diet metabolism and energy balance, gut permeability, intestinal hormone secretion, insulin resistance, and systemic inflammation [ 126 , 127 ].…”
Section: Clinical Management Of Obesitymentioning
confidence: 99%
“…Most of the microbes reside (> 95%) within the gut and maintain intestinal homeostasis[ 53 ]. Dysbiosis of gut microbiota can regulate inflammation and immune response in the TME to promote cancer progression[ 54 , 55 ], including PC[ 56 , 57 ]. A preclinical study showed that gut microbiota can promote PDAC progression by regulating the infiltration and anti-cancer activity of natural killer cells in the TME[ 58 ].…”
Section: Pathogenesis Of Pancreatic Cancer and Relative Molecular Mec...mentioning
confidence: 99%